Caries preventive efficiency of therapeutic complex accomponying orthodontic treatment of children with initial dental caries. - Denga, A. E. (Medicni Perspektivi, 2013)
The use of orthodontic non-removable appliance in orthodontic treatment interferes with the process of teeth mineralization, worsens level of oral cavity hygiene, stimulates development of caries process. The situation is complicated when a patient has an initial tooth decay. The aim of this study was to determine genetic characteristics of children with initial caries and clinical evaluation of effectiveness of the developed caries preventive therapeutic complex accompanying treatment of jaw facial anomalies (JFA). 47 children aged 12-14 with initial tooth decay participated in the examination. Complex diagnostics, including molecular genetic studies was carried out. Therapeutic complex for children, of the main group included remineralizing, adaptogenic, biogenic agents, which increase non-specific resistance, as well as infiltration ICON therapy before fixing braces. Caries preventive complex accompanying JFA treatment in children with primary tooth decay developed with regard to revealed genetic disorders of amelogenesis, 2-nd of phase detoxification, collagen formation, functional responses in the oral cavity, state of hard tissues of teeth and periodontal tissues enabled to preserve existing carious process, normalize periodontal and hygienic indices at all stages of treatment.